(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2009)
Incidence of gastric carcinoma as well as other gastric malignancies is increasing day by day in the whole world as well as in Bangladesh. Prevalence of Helicobacter pylori in this country is an important contributing factor in this increasing trend of gastric malignancies. A study was carried out at the Department of Histopathology, Delta Hospital Limited, Dhaka to find out patterns of gastric malignancies in Bangladesh. All endoscopic gastric biopsy received during the stipulated period from January to December 2007, irrespective of age, sex and clinical suspicion, samples were included in the study. During the period total 1543 gastric biopsy samples were received, which were 7.95% of all the received (19410) samples. The endoscopic gastric biopsy samples were received from almost all the geographic locations of Bangladesh. Among those 5 (0.3%) samples were discarded from the study due to superficial inadequate biopsy. Out of 1538 cases 636 (41.35%) cases were malignant neoplasm of stomach, 493 (32.05%) were chronic active gastritis, 150 (9.75%) were chronic gastritis with intestinal metaplasia, 208 (13.52%) were chronic peptic ulcer, 48 (3.12%) were gastric polyp and 11 (0.72%) others. Among 636 gastric malignancies 625 (98.27%) were gastric adenocarcinoma and 11 (1.73%) were non Hodgkin’s lymphoma. Most 357 (57.12%) of the gastric adenocarcinomas were poorly differentiated, 80 (12.8%) were well differentiated and 84 (13.44%) were moderately differentiated. Out of 625 cases, 104 (16.64%) cases were mucin secreting adenocarcinoma. Out of 11 Non Hodgkin’s Lymphoma cases 10 were male and 01 was female. For adenocarcinoma male and female ratio was 2.36:1. Among the gastric carcinoma group the youngest person affected was of 16 year and the oldest person was of 100 year with the mean age 43.14 year. Among the Non Hodgkin’s lymphoma group the mean age was 45 year with the range from 22 year to 65 year. Among the gastric malignancies, 275 (44%) cases were from Chittagong division, 188 (30.08%) from Dhaka division, 108 (17.28%) from Rajshahi division, 58 (9.28%) from Khulna division and others from Sylhet and Barisal division. It reflects very high incidence of gastric malignancies in comparison to other pathological changes in gastric endoscopic biopsy. It also reflects that between 16 year to 100 year no age is immune to the disease. Key Words: Histopathologic pattern, Gastric carcinoma. doi: 10.3329/jafmc.v5i1.2846 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.21-24